Vocational Education and Training: The Northern Territory's history of public philanthropy - Zoellner, Don (ANU Press, 2017)
This book represents the first consolidated history of vocational education and training in the Northern Territory. Not only does the story present a chronological account of events, people and institutions, it also offers an explanation of how the system actually works and this has application well beyond the Territory. The mix of historical accounting and operational analysis comes from a unique perspective. It is proposed that the best way to understand the behaviour of the government ministers who have responsibility for vocational training is to compare their decisions and actions with those of wealthy philanthropists.